Dendritic synaptome of calcium-binding protein containing GABAergic interneurons in the mouse primary visual cortex - Talapka, Petra; Kocsis, Zsolt; Marsi, Lívia Diána; Szarvas, Vera Etelka; Kisvárday, Zoltán (Frontiers in Neural Circuits, 2025)
This article aims to provide a synaptic input database called, dendritic synaptome for dendrites of calcium-binding protein-containing interneurons [calbindin-D28K (CB+), calretinin (CR+), parvalbumin (PV+)] employing a modified correlated light and EM method, the “mirror-technique” that allows for investigating neuronal compartments while preserving utmost ultrastructural quality (Talapka et al., 2021). Nine dendrites and all presynaptic boutons (n = 815) impinging on their surface were traced and reconstructed in three-dimensions (3D) using serial section transmission electron microscopy (ssTEM). The following basic parameters of the synapses were determined: The ratio of symmetric (“ss” or putative inhibitory) and asymmetric (“as” or putative excitatory) synapses, the number of synapses per unit length of dendrite (i.e., density of “as” and “ss”), surface area and volume of presynaptic boutons, and area of the active zones of synapses. Significant differences in the morphometric parameters of asymmetric, but not in symmetric, synapses were detected between the three interneuron subtypes. Surface extent and the number of synapses on PV+ dendrites were the largest compared to the other two subtypes. Although the distribution of presynaptic boutons differed between dendrites, clustering of the presynaptic boutons could be revealed only for PV+ dendrites. Based on our serial-section electron microscopy (ssEM) reconstructions and corresponding light microscopy (LM) databases of CBP dendrites, it was calculated that on average a single CB+, CR+, and PV+ interneuron receives 2,136, 2,148, and 2,589 synapses, respectively, of which 74.6, 81.5, and 85.3% are excitatory, that is, asymmetric, and the remaining inhibitory, that is, symmetric. Carriage return findings provide essential quantitative information to establish realistic computational models for studying the synaptic function of neuronal ensembles in the mouse primary visual cortex.